2021
DOI: 10.1002/cam4.4430
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib for Taiwanese patients with unresectable hepatocellular carcinoma after sorafenib failure: Impact of alpha‐fetoprotein levels

Abstract: Background and Aims Regorafenib has demonstrated its survival benefit for unresectable hepatocellular carcinoma (uHCC) patients in a phase III clinical trial. We aimed to assess the efficacy and tolerability of regorafenib and the predictors of treatment outcomes in Taiwanese patients. Methods We analyzed the survival, best overall response, predictors of treatment outcomes, and safety for uHCC patients who had tumor progression on sorafenib therapy and received regorafenib as salvage therapy between March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Lastly, a higher CLIP score was associated with increased mortality in our study. Although our analysis did not establish an independent association of tumor morphological parameters or the presence of splenic vein thrombosis, the integration of these parameters in the CLIP score suggested a potential association, as supported by Hsu et al's study, which demonstrated increased mortality with a higher CLIP score [ 36 ]. Our analysis indicated that among patients with Child-Pugh class B, the risk of death was 1.21 times higher compared to those with Child-Pugh class A. Additionally, although not statistically significant, the risk of death was 2.81 times higher in patients with Child-Pugh class C compared to those with class A, aligning with findings reported by Hassan-Kadle et al [ 37 ].…”
Section: Discussionmentioning
confidence: 46%
“…Lastly, a higher CLIP score was associated with increased mortality in our study. Although our analysis did not establish an independent association of tumor morphological parameters or the presence of splenic vein thrombosis, the integration of these parameters in the CLIP score suggested a potential association, as supported by Hsu et al's study, which demonstrated increased mortality with a higher CLIP score [ 36 ]. Our analysis indicated that among patients with Child-Pugh class B, the risk of death was 1.21 times higher compared to those with Child-Pugh class A. Additionally, although not statistically significant, the risk of death was 2.81 times higher in patients with Child-Pugh class C compared to those with class A, aligning with findings reported by Hassan-Kadle et al [ 37 ].…”
Section: Discussionmentioning
confidence: 46%
“…A search of the PubMed database identified 24 cohorts in 23 studies encompassing 2074 patients treated with REG (Figure 1 and Table ) 11,14–35 . Similarly, six cohorts from six studies comprising 621 patients treated with RAM 12,36–40 were identified, as well as seven cohorts from six studies involving 1240 patients treated with CAB 13,23,33,41–43 (Figure 1 and Tables and , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…AI is starting to facilitate this role in recent years (Table 4). For instance, Hsu et al utilized a decision tree-based survival predictive model using a random forest algorithm to assess how serum biomarkers, such as AFP, albumin-bilirubin (ALBI) grade, and circulating angiogenic factors predict the efficacy of lenvatinib in patients with unresectable HCC [54]. The study found that a reduction in AFP ≥ 40% from baseline within 8 weeks posttreatment was associated with a higher objective response rate (ORR).…”
Section: The Role Of Ai In Facilitating Biomarkers To Predict the Eff...mentioning
confidence: 99%